HUBUNGAN PENGETAHUAN DENGAN MOTIVASI IBU HAMIL MELAKUKAN SENAM HAMIL DI PUSKESMAS KARYA WANITA RUMBAI PEKANBARU - Yulita, Emi (Ensiklopedia of Journal, 2018)
Pregnant gymnastics is gymnastics carried out during pregnancy with the aim of preparing the physical and mental of pregnant women, with the hope that the birth process will run smoothly and safely. The purpose of the study was to determine the relationship between knowledge and motivation of pregnant women to do pregnancy exercise. This research is an analytical study with a cross sectional approach carried out at the Pekanbaru Women's Health Work Center. Sampling was done by accidental sampling to 26 respondents. Before this research was conducted, it had conducted validity and reliability tests on 20 respondents at the Umban Sari Rumbai Pekanbaru Health Center. The results showed that there was a significant relationship between knowledge and motivation of pregnant women doing pregnancy exercises (P value 0,000